Disrupting Colonial Narratives: (Re)claiming Autonomy and (Re)affirming Traditional Family Structures through Story in the Teme-augaming - Rowe, Robyn K. (Health Reform Observer - Observatoire des Réformes de Santé, 2024)
Land displacement, theft, and erasure have been key drivers in undermining the political, economic, cultural, linguistic, ancestral, and family formations of First Nations people in Canada. Nation rebuilding is the cornerstone of all sovereignty efforts and is a necessary component of improving the social and political conditions that impact health and wellness. Exercising sovereignty is tightly linked to the autonomous assertion of land and resource rights. Discrimination through the Crown’s self-imposed position as the natural owner of all land and resources across the country is evidenced by a continued failure to recognize the many ways that First Nations self-identify. This inadequacy overlooks First Nations’ inherent rights to self-determination while advancing colonial ideologies. This paper presents a thread of qualitative research findings from a project that included an Indigenous storywork method with one First Nations’ Elder and grandmother, kookum. Within the context of her-story and traditional knowledge mobilization, this work challenges the colonially defined territorial boundaries of the hereditary family clan structures across the Temagami region in Northeastern Ontario, Canada. Kookum’s story demonstrates how colonial policies and practices undermine hereditary conceptions of traditional family identity and led to the misguided and unauthorized theft of the Friday family territories. The reconstruction of identity damages hereditary forms of governance and impairs traditional and familial connection to land, culture, language, and traditions, and is 1) incompatible with self-determination; 2) maintains and perpetuates colonialism; 3) hinders genuine reconciliation; and 4) furthers health and socio-economic inequities for First Nations people. Le déplacement, le vol et l’effacement des terres ont été les principaux facteurs qui ont miné les formations politiques, économiques, culturelles, linguistiques, ancestrales et familiales des peuples des Premières nations du Canada. La reconstruction de ...